A sulfated glucuronorhamnan from the green seaweed Monostroma nitidum: Characteristics of its structure and antiviral activity. (1st January 2020) - Wang, Shuyao; Wang, Wei; Hou, Lukuan; Qin, Ling; He, Meijia; Li, Wenmiao; Mao, Wenjun
Highlights: A homogeneous polysaccharide (MWS) was isolated from the green alga Monostroma nitidum . MWS is a sulfated glucuronorhamnan with sulfate groups at rhamnose residues. MWS had broad spectrum antiviral effects against influenza virus, HSV and EV71. MWS inhibited EV71 infection through targeting PI3K/Akt pathway or virus particle. MWS could be a potential antiviral agent. Abstract: A water-soluble polysaccharide from Monostroma nitidum, designated MWS, was isolated using water extraction, anion-exchange and size-exclusion chromatography. MWS was a sulfated glucuronorhamnan consisting of →3)-α-l -Rha p -(1→, →4)-β-d -Glc p A-(1→ and →2)-α-l -Rha p -(1→ units. Sulfate ester groups located at C-4/C-2 of →3)-α-l -Rha p -(1→ and C-4/C-3 of →2)-α-l -Rha p -(1→ units. In in vitro tests, it was proved that MWS possessed broad spectrum against different viruses, especially for enterovirus 71 (EV71) with nearly no toxicity in relation to cell lines used. MWS may largely inhibit EV71 infection before or during viral adsorption through binding to virus particles and block some early steps of virus life cycle by down-regulating host phosphoinositide 3-kinase /protein kinase B signaling pathway. Intramuscular injection of MWS markedly reduced viral titers in EV71-infected mice. The data demonstrated that MWS could have great promising to become an antiviral drug for prevention and therapy of EV71 infection.